2018
DOI: 10.1371/journal.pone.0190620
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein E may be a novel biomarker of migraine

Abstract: Migraine attacks alter various molecules that might be related to the pathophysiology of migraine, such as serotonin, calcitonin gene-related peptide, and nitric oxide. The underlying pathophysiology of migraine is as yet unclear. We explored key proteins related to the pathogenesis of migraine here. Serum was collected from two patients with migraine with aura (MA) and seven patients with migraine without aura (MO) during attack-free periods and migraine attacks. Samples were analyzed using 2-dimensional gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…On the other hand, monocyte and MHR values were significantly higher in MwA patients. In the literature, some inflammatory biomarkers such as high leptin, Soluble urokinase plasminogen activator receptor, apolipoprotein E, and CRP levels were found to be increased in MwA patients supporting the inflammatory hypothesis [24][25][26][27]. Further studies with serum markers and inflammatory citokines are needed to evaluate the possible relationship.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, monocyte and MHR values were significantly higher in MwA patients. In the literature, some inflammatory biomarkers such as high leptin, Soluble urokinase plasminogen activator receptor, apolipoprotein E, and CRP levels were found to be increased in MwA patients supporting the inflammatory hypothesis [24][25][26][27]. Further studies with serum markers and inflammatory citokines are needed to evaluate the possible relationship.…”
Section: Discussionmentioning
confidence: 95%
“…Serum profiles of patients with different chronic pain conditions (such as fibromyalgia, chronic widespread pain and painful neuropathies) were associated with abnormal levels of varying protein molecules (16,17), some appear capable of diagnosing endometriosis in patients suffering from chronic pelvic pain (18). Also, in migraine, different proteins were detected in the attack period compared to the attack-free period using 2-DE and MS analysis (19). Theor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased levels of ApoE were observed among patients with migraine in the interictal period when compared to controls. 22 A study by Ferrari et al has shown increased levels of serotonin during attacks of migraine as compared to the baseline or controls. 23 Melatonin is believed to be involved in circadian rhythms and headache disorders.…”
Section: Circulating Biomarkersmentioning
confidence: 99%